Effects of nano-SiC addition on the superconducting properties of magnesium diboride - Tan, Kwee Yong; Tan, K. L.; Tan, Kar Ban; Lim, K. P.; Shaari, Abdul Halim; Chen, Soo Kien (Malaysian Solid State Science and Technology Society, 2012)
In this study, we report the results on phase formation, microstructures, and superconducting properties of a series of MgB2 samples with different level of SiC additions. The polycrystalline samples were prepared via solid state reaction by mixing magnesium, boron and silicone carbide powders according to the ratio of Mg:B:SiC = 1:2:x. XRD spectra showed that MgB2 is the primary phase while Mg2Si, MgO and MgB4, together with some unreacted SiC are the secondary phases as the addition increases. The presence of Mg2Si became more significant as the addition level increased. SEM images showed smaller grains as the addition level increases indicating more grain boundaries were formed. The Tc was as low as 30.5K for x=15wt%. The field dependence of Jc showed that x=1wt% sample gave the best performance at both 5K and 20K.